NON-OSSEOUS UPTAKES OF TC-99M PHOSPHONATE DURING THREE PHASE BONE SCAN - Taher, M.A. (The ASEAN Journal of Radiology, 2023)
Objective : The purpose of this study was to visualize non-osseous uptakes of bone scanning agent. Methods : Amongst 51 patients (M21, F30) of age range 8-80 years having three phase bone scan at NNC, Rangpur during January 2000 to January 2002, we looked for non-osseous uptake. Results : Twenty four patients had non-osseous uptakes of 99 metastable technetium methylenediphosphonate (99m Tc MDP), 19 in kidneys (14 in right, 4 in left kidney, one patient showing hold-up in both kidneys), 3 in breasts (2 in left, 1 in right breast), and two patients had lung uptakes. Renal, pulmonary and mammary uptakes of this series are not always due to malignant process, however, one patient had cisplatin nephrotoxicity. Conclusion : Non-osseous uptake of bone-seeking radiopharmaceutical is quite common (24/51 i.e. about 48% in this series), however, most of these may be nonmalignant.